The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4314/sjms.v5i1.56023
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Pattern of Neonates Admitted into Nursery Unit in Wad Medani Hospital, Sudan

Abstract: Background: Neonatal outcome is an important indicator of obstetrics and health care. Few or no published data are available concerning neonatal morbidity and mortality in Sudan. Objectives: To study morbidity and mortality pattern amongst inborn neonates admitted into nursery unit in Wad Medani Hospital, Sudan during the period Jan-June, 2009. Results: A total of 1211 (29.5%) out of 4098 in-born neonates were admitted during study period. The major indications for neonatal admission were; infections 300 (24.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
4
14
1
Order By: Relevance
“…These results of high neonatal mortality are similar to that of an earlier study [ 15 ] which showed an early neonatal death of 10.9%, as well as results of a study at a regional referral hospital in Sudan where also only inborn neonates were included [ 21 ]. The results are also similar to those of a study on newborns admitted to the NICU in Tanzania in 2003 [ 22 ], which reported a 19% neonatal mortality, as well as those of a study from Nigeria [ 23 ] which showed a neonatal mortality rate of 20.3%.…”
Section: Discussionsupporting
confidence: 89%
“…These results of high neonatal mortality are similar to that of an earlier study [ 15 ] which showed an early neonatal death of 10.9%, as well as results of a study at a regional referral hospital in Sudan where also only inborn neonates were included [ 21 ]. The results are also similar to those of a study on newborns admitted to the NICU in Tanzania in 2003 [ 22 ], which reported a 19% neonatal mortality, as well as those of a study from Nigeria [ 23 ] which showed a neonatal mortality rate of 20.3%.…”
Section: Discussionsupporting
confidence: 89%
“…The proportional Preterm mortality was more than that of term babies. In our study, out born deaths (Table 4) were significantly higher than that of inborn babies which are similar to other studies [10,11]. The probable cause for increased in number of out born deaths could be due to delayed referrals.…”
Section: Discussionsupporting
confidence: 91%
“…Of 2089 neonates admitted to NICU, 1978 (94.68%) neonates were discharged home, when compared to other studies which have reported 81% and 82% discharges [10,11]. During this study period there were 71 deaths.…”
Section: Discussionmentioning
confidence: 65%
“…Outcome of 1580 admitted babies (Figure2) 83%were discharged home, very similar to studies which reported 81% and 82% discharges [7,11]. These two studies reported DAMA as 7.7% and 4% while a study from Maharashtra reported 31.7% [15].…”
Section: Discussionsupporting
confidence: 67%